Effects of nano-A12O3 on early-age microstructural properties of cement paste - Barbhuiya, Salim; Mukherjee, S.; Nikraz, Hamid (Elsevier BV, 2014)
The effects of nano-Al2O3 addition on the early-age microstructural properties of cement paste is reported in this paper. The study was limited to evaluation of properties of cement paste hydrated up to an age of 7 days. Ordinary Portland cement was replaced by nano-Al2O3 powder at 2% and 4% by weight. The water–binder ratio was fixed at 0.4. No changes were noticed in the early-age compressive strength with nano-Al2O3 addition. XRD analysis confirmed that no new phase developed due to the addition of nano-Al2O3 powder. However, FTIR analysis shows a shift in water associated band to lower frequency mostly with 4% nano-Al2O3 addition. Scanning electron microscopy reveals the formation of much dense microstructure with larger crystals of portlandite within the cement matrix.